Beitrag zur Frage des Universitatsstudiums der Frauen : Rede zum Antritt des Rektorats der Christian-Albrechts-Universitat in Kiel am 6. Marz 1893 - Pochhammer, Leo, 1841- (Universitats-Buchhandlung, 1893)
A lecture given by Pochhammer on the occasion of his becoming Rektor of the University of Kiel. His discussion of whether women should be admitted to the universities analyzes the areas in which women should be allowed and debates the idea of separate universities for women.